2022
DOI: 10.1101/2022.03.04.483032
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chimeric mRNA based COVID-19 vaccine induces protective immunity against Omicron and Delta

Abstract: The emerging SARS-CoV-2 variants of concern (VOCs) exhibit enhanced transmission and immune escape, reducing the efficacy and effectiveness of the two FDA-approved mRNA vaccines currently in use. Here, we explored various strategies to develop mRNA vaccines that offer potentially safer and wider coverage of VOCs. The initial mouse vaccination results showed that the individual VOC mRNAs carrying furin cleavage mutation induced the generation of neutralizing antibody in a VOC-specific manner. Moreover, we disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
3
4
0
1
Order By: Relevance
“…Other groups could show that the T‐cell and antibody responses against SARS‐CoV‐2 spike glycoprotein remain effective against the currently dominating B.1.1.529 VoC. 45 , 87 , 88 , 89 , 90 We support these observations in this high‐resolution analysis. We found that every individual in our study still had at least seven CD4 + T‐cell specificities that were conserved in all VoCs and LUMs investigated.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Other groups could show that the T‐cell and antibody responses against SARS‐CoV‐2 spike glycoprotein remain effective against the currently dominating B.1.1.529 VoC. 45 , 87 , 88 , 89 , 90 We support these observations in this high‐resolution analysis. We found that every individual in our study still had at least seven CD4 + T‐cell specificities that were conserved in all VoCs and LUMs investigated.…”
Section: Discussionsupporting
confidence: 76%
“… 43 , 44 This raises the question of whether vaccination with wild‐type spike glycoprotein primes sufficient cross‐reactive T‐cell responses. 27 , 45 Incidentally, subject HH‐SP‐26, who was infected with the B.1.1.529.1 variant, showed a similar number of spike‐specific CD4 + T‐cell responses compared to patients infected with other virus variants. Even under the assumption that there was no cross‐reactivity between a wild‐type peptide specificity that differs at any amino acid position for the B.1.1.529 VoC, there would be considerable T‐cell responses: Even if all peptides with any mutational change were not counted as a potential response, there would still be at least seven responses attributable in conserved regions and peptide sequences for every patient (median 21; range 7–35) (Supplementary figure 6a, b ).…”
Section: Resultsmentioning
confidence: 97%
“…Conversely, Omicron BA.1 infection alone offers limited protection against pre-Omicron and against Omicron BA.2-related strains, while breakthrough infection after vaccination confers some cross-protection [95]. These results are in line with the observation that Omicron BA.1 variant-based vaccines including Delta determinants have higher neutralizing ability against Omicron sublineages compared to vaccines which include only Omicron determinants [116,120]. They also indirectly confirm the serologic similarities between B.1 and Delta (Fig 1B and 1D and Fig 3A , 3D and 3E) on one hand and the serotypic specificity of the Omicron lineage and sublineages on the other.…”
Section: Discussionsupporting
confidence: 74%
“…The fact that booster strategies based on pre-Omicron VOCs Beta or Delta did not neutralize Omicron BA.1 better than the wild-type booster [ 80 ] lends further support to this view. In contrast, heterologous Omicron BA.1-based booster vaccines [ 130 ] and bivalent booster vaccines based on wild-type + Omicron BA.1, Delta + Omicron BA.1 or hybrid Omicron BA.1/Delta determinants induce higher neutralizing humoral responses and T-cell responses against all Omicron sublineages as well as against pre-Omicron VOCs than homologous (wild-type) or pre-Omicron (Beta or Delta) booster vaccines in humans and mice [ 80 , 117 , 131 , 132 , 133 ]. Our results also indirectly confirm the serologic similarities between B.1 and Delta ( Figure 1 B,D and Figure 3 A,D,E) on one hand and the serotypic specificity of the Omicron lineage and sublineages on the other.…”
Section: Discussionmentioning
confidence: 99%